The Relationship Between Self-Control and Intensity of Social Media Use in Late Adolescents in University: Hubungan Antara Kontrol Diri dengan Intensitas Penggunaan Sosial Media pada Remaja Akhir di Universitas - Rahma, Alifia; Laili, Nurfi (Indonesian Journal of Education Methods Development, 2022)
This research is motivated by the phenomenon of the intensity of social media use experienced by adolescents. This study aims to determine the relationship between self-control and the intensity of social media use in late teens. This research is included in the type of quantitative research with a correlational approach. The population in this study were all late teens at the Faculty of Psychology and Education, Muhammadiyah University of Sidoarjo with a total of 2160 people. The sample in this study was 297 people with purposive sampling technique. The data collection technique in this study used a self-control scale and a social media use intensity scale. The data analysis technique uses the product-moment relationship using SPSS16.0. The results of the data analysis of this study explain that the value of the relationship coefficient (rxy) is -0.382 using a significance of 0.000 <0.05 which indicates that there is still a significant negative interaction between self-control on the intensity of social media use in late teens. The effect of self-control on the intensity of social media use in this study was 14.6%.